Impact of uniform and Gaussian intracellular activity distribution on DNA damage: a Geant4-DNA study of Auger electron–emitting radionuclides in V79 cells - Ali Azizi Ganjgah; Payvand Taherparvar; Ioanna Kyriakou (Physics in Medicine & Biology, 2026)
Abstract Objective: Auger electron (AE)-emitting radionuclides are highly sensitive to subcellular localization, and even small variations in intracellular distribution can substantially alter DNA damage. Accordingly, this study quantitatively evaluates the influence of radionuclide type, target-source configuration, and, as a novel feature, the effect of intracellular spatial distribution on the DNA strand breaks using Geant4-DNA.
Approach: A detailed V79 cell model containing atomistic chromatin fibers was implemented in Geant4-DNA. Five AE-emitting radionuclides (99mTc, 111In, 123I, 125I, and 201Tl) were simulated under two target←source configurations (N←N and N←C) and both uniform and Gaussian (standard deviation (σ) = 0.5-3.5 μm) spatial distributions. Direct and indirect DNA strand breaks were quantified.
Main results: Spatial confinement of activity exerted a quantitatively substantial, damage-type-dependent influence on DNA strand breaks. In the N←N, reducing from a uniform distribution to a Gaussian one (σ= 0.5 μm) increased DSB (HDSB) yields by up to 33% (~38%). This differential response, where complex lesions are disproportionately amplified by spatial heterogeneity relative to simple breaks, reflects the nanometer-scale co-localization required for clustered damage formation and was consistently observed across all radionuclides. N←N configuration resulted in ~44% higher deposited energy compared to N←C. In terms of DNA damage ranking, 201Tl produced the highest yields across all configurations, with deposited energy up to 36% (over 3000%) greater than 125I (99mTc), consistent with its high AE multiplicity and mean energy per decay.
Significance: The findings demonstrate that, for the idealized nucleus-centered truncated Gaussian distributions, increased spatial confinement enhances the formation of complex DNA lesions relative to uniform distributions. These results indicate that assuming uniform distributions may underestimate complex DNA damage for such confined source distributions. However, the conclusions are limited to the specific Gaussian models investigated and should not be generalized to other biologically realistic heterogeneous uptake patterns.